Implementation of the PIECES Method in the Student Assessment System of SMPN 201 Jakarta - Sara Yemima Br Ambarita; Sugeng Sugeng (Eduvest - Journal of Universal Studies, 2021)
The development of technology has developed very rapidly along with the many human needs. Web technology systems are one of the most frequently used applications in everyday human life. Assessment in the learning process is important, so that good value data processing will produce report cards as a good evaluation result, besides that the results of value data processing will be used as one of the benchmarks for the success of students taking education in school. This study aims to implement the PIECES method at the stage of developing a student assessment system at SMPN 201 Jakarta in the form of a web application. PIECES analysis consists of Performance, Information, Economy, Control, Efficiency and Service. The conclusion of the research is that the application of a multi-user student assessment data system application at SMPN 201 Jakarta can improve work services and time efficiency in terms of processing student grade data. The student assessment data processing system using analysis using the PIECES method in a multi-user manner aims to make a computerized system in schools able to integrate all recording activities that are carried out manually and require office stationery (ATK) to be minimized.